DENTAL ANXIETY – A PSYCHOSOCIAL CAUSE AFFECTING THE QUALITY OF LIFE – A SYSTEMATIC REVIEW - Andreea Sălcudean; Laria-Maria Trușculescu; Ramona Amina Popovici; Nicoleta Șerb; Ciprian Pașca; Cristina Raluca Bodo; Ramona Elena Crăciun; Iustin Olariu (Romanian Journal of Oral Rehabilitation)
Dental anxiety is a prevalent psychosocial issue that significantly affects the quality of life for many individuals, influencing their willingness to seek dental care and ultimately affecting their oral health.